Analisis Campur Kode Bahasa Batak Pada Saat Pembelajaran di Kelas X SMA YAPIM Merek Tahun Ajaran 2023/2024 - Vina Octavia Kudairi; Tri Indah Kusumawati; Budiman Budiman (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The research was carried out with the title "Analysis of Batak Language Code Mixing When Learning Indonesian in Class The use of code mixing is the Batak regional language. The aim of this research is to determine the main causes of the use of code mixing during learning. This research methodology is a qualitative descriptive method. Data was obtained from class X students of YAPIM Brand High School and the results of interviews from Indonesian language teachers. Data collection techniques were carried out by interviewing, recording and taking notes. The results of this research are forms of code mixing in teacher and student conversations in Indonesian language learning in class X SMA YAPIM Brand, namely: a. Use of Toba Batak language code mixing, b. There are 76 code-mixed data, the forms of code-mixing use are 13 code-mixes of word insertion, 17 phrase insertions, 46 clause insertions, word and sentence insertions. Factors causing code mixing are: a. Students' proficiency in speaking two languages, including the Toba Batak regional language and Indonesian, b. Social environment, c. Contextual situation. However, Indonesian language interference is not eliminated by the presence of the regional language, it's just that students sometimes focus more on using the regional language instead of being in context when speaking with fellow students.